2016
DOI: 10.11607/jomi.4932
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Cohort Study of 4,591 Straumann Implants Placed in 2,060 Patients in Private Practice with up to 10-Year Follow-up: The Relationship Between Crestal Bone Level and Soft Tissue Condition

Abstract: The purpose of this report is to describe the crestal bone level (CBL) around implants of various designs, describe the peri-implant soft tissue condition, and evaluate the relationship between the two over time. Materials and Methods: This retrospective cohort study reports on 2,060 patients with 4,591 implants evaluated after 3 months; 1, 3, 5, and 7 years; and up to 10 years. Periapical radiographs were used to evaluate changes in CBL. The peri-implant soft tissue was evaluated using a modified Bleeding Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 44 publications
3
44
0
2
Order By: Relevance
“…Interestingly, implants placed in an incorrect bucco‐lingual position (thin buccal bone) were more prone to be associated with more overt clinical signs and hence to a more definitive disease diagnosis. Moreover, the present study tested two indexes proposed in the classic and recent literature for assessing marginal mucosal conditions . Both indexes demonstrated to be reliable for monitoring peri‐implant conditions, since both were strongly correlated to the progression of bone loss.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, implants placed in an incorrect bucco‐lingual position (thin buccal bone) were more prone to be associated with more overt clinical signs and hence to a more definitive disease diagnosis. Moreover, the present study tested two indexes proposed in the classic and recent literature for assessing marginal mucosal conditions . Both indexes demonstrated to be reliable for monitoring peri‐implant conditions, since both were strongly correlated to the progression of bone loss.…”
Section: Discussionmentioning
confidence: 91%
“…based the assessment of marginal mucosal condition on the presence and severity of edema, redness, glazing, ulceration, and bleeding with or without probing. More recently, French et al . modified the original scale described by Mombelli et al .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore obvious that deeper pockets have a higher tendency to bleed. A recent large retrospective cohort study (French et al., 2016) of nearly 5,000 Straumann implants placed in 2,060 patients with up to 10‐year follow‐up concluded that time alone and minimal bleeding did not correlate with bone loss but that care should be taken for implants with profuse bleeding or suppuration. They found the highest mean bone loss around implants with suppuration and minor changes for implants with minimal to moderate or profuse bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…This latter finding is in accordance with the results of the study of French et al. (2016). They specified that suppuration was detected in implants with the highest bone loss and suggested it could be useful for clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation